URGENSI KETELADANAN GURU DALAM MEMBENTUK GENERASI ALPHA BERKARAKTER PANCASILA DI SEKOLAH DASAR - Ad Dauwi, Anastya; Yohamintin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Alpha Generation, currently attending elementary school, holds a crucial role as the nation's future leaders who will shape the direction of Indonesia. Therefore, it is essential to develop effective approaches to instill Pancasila values in students. This study aims to provide an in-depth overview of teachers' role modeling in shaping Pancasila character in Alpha Generation students at the elementary school level. A qualitative approach with a case study method was used, involving principals, teachers, and students as participants. Data were collected through observation, interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that the formation of Pancasila character is carried out through two main approaches: teacher role modeling and the implementation of character values in learning activities and the school environment.